Geographical prevalence and risk factors for pterygium: a systematic review and meta-analysis - Zhe Yuan; Lei Liu; Jingyang Wu; Desheng Huang; Jin Geng (BMJ Open)
Objective Pterygium is considered to be a proliferative overgrowth of bulbar conjunctiva that can induce significant astigmatism and cause visual impairment; this is the first meta-analysis to investigate the pooled prevalence and risk factors for pterygium in the global world.Design A systematic review and meta-analysis of population-based studies.Setting International.Participants A total of 20 studies with 900 545 samples were included.Primary outcome measure The pooled prevalence and risk factors for pterygium.Results 20 studies were included. The pooled prevalence of pterygium was 10.2% (95% CI 6.3% to 16.1%). The pooled prevalence among men was higher than that among women (14.5% vs 13.6%). The proportion of participants with unilateral cases of pterygium was higher than that of participants with bilateral cases of pterygium. We found a trend that the higher pooled prevalence of pterygium was associated with increasing geographical latitude and age in the world. The pooled OR was 2.32 (95% CI 1.66 to 3.23) for the male gender and 1.76 (95% CI 1.55 to 2.00) for outdoor activity, respectively.Conclusions The pooled prevalence of pterygium was relatively high, especially for low latitude regions and the elderly. There were many modifiable risk factors associated with pterygium to which healthcare providers should pay more attention.